Increased vulnerability to psychological distress and suicidal ideation among transgender women with self-reported disabilities in San Francisco, California - Abtin Shafie; Alexis Salvatore; Riley Shea; Eileen Yu; Oyku Ozyucel; Ansharan Akbar; Bow Suprasert; Erin C. Wilson; Willi McFarland; Kelly D. Taylor; Sean Arayasirikul (Preventive Medicine Reports)
OBJECTIVE: Research among transgender women has found health, but especially mental health, to be shaped by social inequities and multiple, intersectional, structural vulnerabilities. While some studies have shown that transgender adults are also more likely to have a disability than cisgender adults, few studies have explored this intersection. We assess possible associations between disability status and psychological stress and suicidal ideation among transgender women. METHODS: We analyzed data from the San Francisco site of the National HIV Behavioral Surveillance Transgender (NHBS-Trans) Study (2019–2020) to explore how disability status among transgender women influences mental health. Chi-squared and Fisher's exact tests to assess associations between disability status and psychological distress. Multivariable logistic regression models assessed the magnitude of these associations adjusted for potential confounders. RESULTS: 71.14 % of the sample (N = 201) reported living with one or more disabilities. Participants with 1+ disabilities had more than 10 times the odds of reporting high levels of psychological distress (aOR 10.46, 95 % CI 3.06–35.74) and more than five times the odds of reporting suicidal ideation (aOR 5.83, 95 % CI 1.69–20.15) compared to those with no disabilities. Participants with 2+ disabilities had 10+ times the odds of reporting suicidal ideation compared to participants with no disabilities (aOR 10.77, 95 % CI 2.94–39.51). CONCLUSIONS: Transgender women living with disabilities face multiple intersecting inequities likely attributable to living in a world that is not built for them on the basis of gender identity and disability status. The resulting psychological distress, alongside transphobia and ableism, can exacerbate mental health issues.